Situation Report: Bulgaria, 31 July 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Agreement on Nish-Dimitrovgrad Road Signed The Electric Railroad Sofia-Plovdiv Finished Kadar Left Bulgaria The New US Envoy Arrived in Sofia